Sygyzium claviflorum fruit extract preadipocyte differentiation inhibition in 3T3-L1 cells - Zohdi, Rozaini M.; Adli, Muhammad A.; Mukhtar, Shahida M.; Awang Junaidi, Awang H.; Bakar, Md Zuki A. (Elsevier B.V., 2024)
Objective: Concerns over the increasing number of obese individuals and the associated health risks have prompted therapeutic option explorations. Similarly, this study aimed to establish Sygyzium claviflorum fruit extract (SCFE) anti-adipogenic attributes in 3T3-L1 cells. Methods: The polyphenolic compounds in SCFE were identified with Reverse phase-high performance liquid chromatography (RP-HPLC). Meanwhile, murine 3T3-L1 preadipocytes, measuring leptin levels, reactive oxygen species (ROS), and lipid and triglyceride (TG) contents were utilized during anti-adipogenic activity assessments. Concurrently, the effects of SCFE on adipogenic transcription factors were established with quantitative real-time-polymerase chain reaction (qRT-PCR). Results: The RP-HPLC results indicated three polyphenolic compounds in SCFE, including one flavonoid (naringin) and two phenolic acids (syringic and p-coumaric). Although SCFE treatments (250–1000 μg/mL) did not result in cell toxicity, they significantly reduced dose-dependent lipid accumulation, ROS production, and TG and leptin levels relative to control-differentiated adipocytes. Moreover, SCFE suppressed sterol regulatory element binding protein-1 (SREBP-1), peroxisome proliferator-activated receptor-gamma (PPAR-γ), and CCAAT/enhancer-binding protein-alpha (C/EBP-α) gene expressions during preadipocyte differentiation into adipocytes. Conclusion: The findings revealed the anti-adipogenic properties of SCFE, indicating its potential as a natural obesity management remedy. Nevertheless, more studies are necessary to elucidate the reactions resulting in SCFE anti-adipogenic effects and the active constituents responsible for the property.